Wartime Notebooks : France, 1940-1944 - Bobkowski, Andrzej (The Margellos World Republic of Letters, 2018)
"When the aspiring young writer Andrzej Bobkowski, a self-styled cosmopolitan Pole, found himself caught in occupied France in 1940, he recorded his reflections on culture, politics, history, and everyday life. Published after the war, his notebooks offer an outsider's perspective on the hardships and ironies of the Occupation. In the face of war, Bobkowski celebrates the value of freedom and human life through the evocation -- in a daringly untragic mode -- of ordinary existence, the taste of simple food, the beauty of the French countryside. Resisting intellectual abstractions, his notes exude a young man's pleasure in physical movement -- miles clocked on country roads and Parisian streets on his trusty bike -- and they reveal the emergence of an original literary voice. Bobkowski was recognized in his homeland as a master of modern Polish prose only after Communism ended. He remains to be discovered in the English-speaking world."--